Effective tube-in-tank PCM thermal storage for CSP applications, Part 1: Impact of tube configuration on discharging effectiveness. (1st December 2016) - Belusko, M.; Tay, N.H.S.; Liu, M.; Bruno, F.
Highlights: A two part study into impact of boundary conditions on heat transfer with PCM. Heat transfer with counterflow was significantly higher than for parallel flow. The phase front has a significant impact on the loss of heat transfer. Abstract: Effective extraction of latent energy is critical in phase change material (PCM) thermal storage applications, including CSP plants. For tube-in-tank arrangements, research to date has not explicitly investigated the impact of the boundary condition applied to the PCM surrounding the tube on the heat transfer process. In Part 1 of this study, the impact of this boundary condition was investigated by applying different tube configurations, defined by the heat transfer fluid either flowing parallel, counterflow or in a serpentine arrangement. The study identified that the critical factor was the loss of heat transfer area experienced once the phase front between parallel tubes meet. This was significant for parallel flow but essentially eliminated for the counterflow arrangement, which delivered a more uniform phase front parallel to the tube wall. As a result it was identified that the amount of redundant PCM when applying the counterflow arrangement was 9%, while this value was 32% for the parallel flow arrangement. This difference has a significant impact on the cost of thermal storage for CSP plants. Part 2 will involve a parametric assessment of the parallel and counterflow configurations.